Avian extinctions induced by the oldest Amazonian hydropower mega dam: Evidence from museum collections and sighting data spanning 172 years - Pinto Henriques, Luiza Magalli; Dantas, Sidnei De Melo; Santos, Lucyana Barros; Bueno, Anderson Saldanha; Peres, Carlos A. (PeerJ, 2021)
Hydroelectric dams represent an emergent threat to lowland tropical forest biodiversity. Despite the large number of operational, under-construction, and planned hydroelectric dams, their long-term effects on biodiversity loss are still poorly documented. Here, we investigate avian extinctions resulting from the Tucuruí Hydroelectric Reservoir (THR), the oldest Amazonian mega dam, which impounded the Tocantins River in 1984. Our avian inventory—based on several sampling methods (mist-netting, point-counts, boat census and qualitative surveys) during 280 days of fieldwork from 2005 to 2007—was combined with an exhaustive search of museum vouchers and digital online databases of citizen science from the lower Tocantins River to identify long-term trends in species persistence and extinction in the THR influence area. The regional avifauna was comprised of 479 species, 404 of which were recorded during our fieldwork. Based on recent and historical records spanning 172 years, we found evidence for likely extinctions at THR influence area for 53 (11.06%) species that have remained entirely unreported since 1984. We were further able to estimate extinction probabilities for 20 species; 15 species were considered to be extinct, including Psophia interjecta and Pyrilia vulturina that are red-listed by IUCN. Our study serves as a baseline for avifaunal monitoring in the THR influence area and shows that degree of habitat specialization is a key factor in determining species extinctions caused by nonrandom habitat loss from either inundation or deforestation. Avian species extinctions will most likely continue across the area affected by the reservoir as a direct impact of alluvial forest loss and ongoing habitat degradation of upland forests. © 2021 PeerJ Inc.. All rights reserved.
Keywords: Article; Bird; Citizen science; Dam (barrier); Deforestation; Ecological specialization; Endangered species; Field work; Forest fragmentation; Hydropower; Information center; International Union for Conservation of Nature; Nonhuman; Probability; River; Species extinction; Tocantins